Cover Feature: Catalytic Dry Reforming of Methane: Insights from Model Systems (ChemCatChem 8/2020). Issue 8 (24th April 2020) - Wittich, Knut; Krämer, Michael; Bottke, Nils; Schunk, Stephan Andreas
Abstract : The Cover Feature illustrates how dry reforming serves as backbone in paving the path towards sustainable olefins. On the left, the pilot reformer is depicted, which serves as a symbol for Linde's DRYREF© process, while the dry reforming catalyst represents BASF's SYNSPIRE© catalyst technology. In their Review, K. Wittich et al. describe how experts from both companies have co‐created the technology that decreases the carbon dioxide footprint in olefin production.More information can be found in the Review by K. Wittich et al. .